Enceleamycins A-C, furo-naphthoquinones from amycolatopsis sp. MCC0218: isolation, structure elucidation, and antimicrobial activity - Khan, Abujunaid; Said, Madhukar S.; Borade, Balasaheb R.; Gonnade, Rajesh; Barvkar, Vitthal; Kontham, Ravindar; Dastager, Syed G. (Journal of Natural Products, 2022)
Three novel furo-naphthoquinones, enceleamycins A-C (1-3), and a new N-hydroxypyrazinone acid (4) were identified from the strain Amycolatopsis sp. MCC 0218, isolated from a soil sample collected from the Western Ghats of India. Their chemical structure and absolute and relative configurations were established by 1D and 2D NMR spectroscopy, single-crystal X-ray crystallography, and high-resolution mass spectrometry. Compounds 1 and 3 were active against methicillin-susceptible and -resistant Staphylococcus aureus with MIC values of 2-16 mu g/mL.